2022
DOI: 10.3390/ijms23094665
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Fatty Acid Amide Hydrolase Inhibitor URB597 on Orofacial Pain Perception in Rats

Abstract: Endocannabinoids act as analgesic agents in a number of headache models. However, their effectiveness varies with the route of administration and the type of pain. In this study, we assessed the role of the fatty acid amide hydrolase inhibitor URB597 in an animal model of orofacial pain based on tooth pulp stimulation. More specifically, we assessed the effects of intracerbroventricular (i.c.v.) and intraperitoneal (i.p.) administration of URB597 on the amplitude of evoked tongue jerks (ETJ) in rats. The level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 81 publications
1
3
0
Order By: Relevance
“…In vitro evidence suggests that CB1 activation can increase Cnr1 mRNA expression via extracellular signal-regulated kinases 1 and 2 (ERK1/2) signaling ( 36 ). Our results are are in agreement with previous studies showing an increase of Cnr1 mRNA expression after 1.5 h of URB597 administration in a pain perception model in rats, although this was evidenced in the mesencephalon, thalamus, and hypothalamus but not in the striatum ( 37 ). Another study also revealed an increase in Cnr1 mRNA expression in the hippocampus after 2 weeks of URB597 treatment in a chronic constriction injury pain model in rats ( 38 ).…”
Section: Discussionsupporting
confidence: 94%
“…In vitro evidence suggests that CB1 activation can increase Cnr1 mRNA expression via extracellular signal-regulated kinases 1 and 2 (ERK1/2) signaling ( 36 ). Our results are are in agreement with previous studies showing an increase of Cnr1 mRNA expression after 1.5 h of URB597 administration in a pain perception model in rats, although this was evidenced in the mesencephalon, thalamus, and hypothalamus but not in the striatum ( 37 ). Another study also revealed an increase in Cnr1 mRNA expression in the hippocampus after 2 weeks of URB597 treatment in a chronic constriction injury pain model in rats ( 38 ).…”
Section: Discussionsupporting
confidence: 94%
“…Furthermore, the section of the nerve in front of the mental foramen and just before its ramification to the incisive nerve has been defined as the anterior loop of the IAN. The IAN transmits pain signals from mandibular teeth, gingiva of the mandible, and the lower lip [43].…”
Section: Introductionmentioning
confidence: 99%
“…
Orofacial pain, with a prevalence of 10%-26%, constitutes a severe medical and social problem. 1 It results from impaired branch of the trigeminal nerve or the spread of neurogenic inflammation to the orofacial region, 1 which is not independent but rather the primary symptom of a group of disorders that occur in the orofacial region with pain. Orofacial pain encompasses dental pain, temporomandibular joint (TMJ) pain, orofacial migraine, trigeminal neuralgia, myofascial pain and mucositis pain.
…”
mentioning
confidence: 99%
“…perceptual, emotional and cognitive) through several routes, such as that involving primary afferent fibres (Aδ and C-fibre), trigeminal ganglion (TG), trigeminal nucleus caudalis (SpVc), and ventral posterior medial nucleus (VPM) and several areas of the cerebral cortex. 1,4,5 In this classic nociceptive pathway, TG or SpVc neurons transcellularly communicate with peripheral glia cells and immune inflammatory cells through various mediators (inflammatory cytokines, neuropeptides and ion channels), receptor mechanisms, and signalling processes, leading to TG or SpVc neuronal hyperexcitability followed by orofacial pain hypersensitivity. 6,7 Among the aforementioned mediators, neuropeptides have been widely studied in the last four decades.…”
mentioning
confidence: 99%